The role of human resource management in the tourism and hospitality industry in south Iceland before, during, and after COVID-19 - Lara Knittel 1990- (2020)
The literature reviewed for this thesis suggests that human resource management (HRM) has a positive impact on organizational performance. However, HRM in the tourism and hospitality industry is characterized by short-term and ad hoc measures and therefore, the industry often struggles with a negative image of employment practices and conditions. The research conducted for this thesis examines how the role of HRM is subject to change before, during, and after the COVID-19 crisis in hotels in south Iceland. A theoretical review introduces the main theories for the research and characteristics of HRM in both crises and the tourism and hospitality industry. Using qualitative research strategy, combined with a short online pre-questionnaire, the role of HRM was examined in nine hotels. The findings revealed that HRM systems are not fully developed in the hotels, and little effort is put into ensuring their development. Only a few HR practices are in place and the COVID-19 crisis has not motivated the participants to undergo a change regarding HRM. Firms in the tourism and hospitality industry could navigate a crisis better if they implement professional HR practices and develop a crisis plan. Furthermore, HRM should be seen as a tool that helps to build a competitive advantage through employees, instead of as a unit that does not provide revenue. The research provides propositions to increase benefit through HRM, as well as how to navigate better through a potential future crisis. Moreover, the conclusion chapter contains limitations to the research and suggestions for future research.